2018
DOI: 10.2217/cer-2017-0057
|View full text |Cite
|
Sign up to set email alerts
|

Comparative effectiveness and patient-centered outcomes research: enhancing uptake and use by patients, clinicians and payers

Abstract: Evidence from comparative effectiveness research (CER) and patient-centered outcomes research (PCOR) studies are increasingly available in the literature. However, there remain opportunities to better integrate that evidence into decision-making. An invitation-only conference held in January 2017, titled “Comparative Effectiveness and Patient-Centered Outcomes Research: Enhancing Uptake and Use by Patients, Clinicians and Payers”, sought to identify and discuss both gaps in the uptake and use of CER/PCOR, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Selecting an appropriate tool to design a valid and meaningful study is imperative, as it directly influences the value of outcome-based research [22][23][24][25][26][27] . Studies examining the nose-related outcomes associated with skeletofacial reconstruction have primarily adopted the 3D morphometric-based objective measure tool 6 .…”
Section: Discussionmentioning
confidence: 99%
“…Selecting an appropriate tool to design a valid and meaningful study is imperative, as it directly influences the value of outcome-based research [22][23][24][25][26][27] . Studies examining the nose-related outcomes associated with skeletofacial reconstruction have primarily adopted the 3D morphometric-based objective measure tool 6 .…”
Section: Discussionmentioning
confidence: 99%
“…As the conference title makes clear, the conference focused on enhancing the uptake and use of CER/PCOR by patients, clinicians and payers. Details of the conference proceedings are found in the two companion papers in this series [16,17].…”
Section: Cer Centers Of Excellence Strategic Evaluationmentioning
confidence: 99%
“…Finally, information processes, including concerns about accessing up-to-date information (Schumock & Pickard, 2018), beliefs about what constitutes evidence (Gupta et al, 2017;Ubel & Asch, 2015), and the source or combination of sources from which the physician receives the evidence (Gupta et al, 2017;Pollack et al, 2017) are likely to impact physician behavior. In one review of the literature on physician behavior change, researchers found that medical decisions are disproportionately influenced by the physicians' mentors (Cunningham et al, 2019).…”
Section: Introductionmentioning
confidence: 99%